PLAGIARISM OCCUR IN STUDENTS’ ACADEMIC WORK, EXPLORING IMPACT THE EFL (ENGLISH as FOREIGN LANGUAGE) UNDERGRADUATE STUDENTS’ PLAGIARISM IN THESES WRITING - La Ode Achmad Suherman; Fathu Rahman; Muhamad Fahmi Eryck; Munirah Munirah (Universitas Lancang Kuning, 2022)
The purpose of this study was to determine how plagiarism occurs within the content of undergraduate EFL thesis submitted by students at a private university in Baubau. The research focuses on instances of accidental plagiarism that may occur on students’ thesis which can be expressed in three distinct ways: How do incorrect citation, quoting, and paraphrasing occur within the content of students' thesis? This study employed a case study in the sense of qualitative method. The thesis served as the sole source of information. The outcomes of this study revealed that some patterns in the evaluated thesis were accidentally plagiarized. It was founded on analysis, which was accomplished via the use of citation, quotation, and paraphrase forms. Incorrectly citation material can be found in the theses of Student 1 (S1), Student 2 (S2), and Student 3 (S3) while Inappropriate quotation can be found in the theses of Student 4 (S4), and Student 5 (S5), and improperly paraphrased material can be found in the theses of Student 6 (S6), and Student 7 (S7). These data indicated that students were lacked understanding of proper citation writing that becomes the main factor of plagiarism occurred.